Budżetowanie środków pieniężnych - procedura i znaczenie jako instrumentu zarządczego - Filipiak, Beata (Cash Budget - Procedure and Meaning as for a Management Instrument, 2006)
The article presents problems of the procedure of preparing and meaning cash budget in management process. The author defined and described particular elements of cash budgeting process in enterprises. There are discussed effects of a cash budget in management process in enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 77-83